Cancer in the older person. Issue 3 (24th August 2015) - Kelly, Emma; Stephens, Peter
Summary: The challenges of treating malignant disease in the elderly population have gained greater prominence over the last 5–10 years. Developed nations all have ageing populations, and cancer in older people is an increasing physical and financial burden on both healthcare systems and populations. When assessing oncology patients, oncologists have traditionally used the Eastern Cooperative Oncology Group or Karnofsky performance status. However, it has been shown that sometimes this does not detect potential problems in older patients, and that a comprehensive geriatric assessment may be a better tool. However good surgeons and oncologists are at adapting their services for older patients, there is little value if they are inappropriately referred or filtered out by either primary or secondary care. Surgery forms the basis of most curative treatment options. The elderly have more peri-operative risk factors including multiple co-morbidities, poly-pharmacy, malnutrition, frailty, cognitive dysfunction and an increased anaesthetic risk, which can create obstacles. Treating older patients with systemic cytotoxic therapy often relies on extrapolating evidence from younger patients. In previous decades, the majority of trials had upper age limits of 65 or 70 years. More recent trials normally include patients of all ages, and entry is based on performance status. Radiotherapy may be chosen as a potentially curative option in patients with an operable tumour, who are unfit. However, oncologists should not underestimate the burden that multiple frequent visits to hospital for treatment may have on an elderly patient population. This article looks at the assessment of elderly oncology patients, referral patterns, surgery, systemic therapies, radiotherapy, supportive therapies and long-term side-effects from treatment.